Educational Interventions for Peace: Transformation of Perceptions and Construction of Life Projects in Hybrid Learning Ecosystems with Cross-Cutting Impact in Post-Conflict Rural Contexts in Colombia - Marcela, Benítez Mendivelso; Andrés, Sánchez Jaramillo Carlos; Catalina, Caicedo Vásquez (Journal of Ecohumanism, 2024)
The long history of armed conflict in Colombia has left a deep mark on rural areas, especially affecting young people, who have had to face the direct and indirect consequences of violence, displacement and social exclusion. This article aims to integrate the results of two previous studies conducted in the municipality of Pradera, Valle del Cauca, to explore how educational interventions, particularly hybrid learning ecosystems, can transform perceptions about armed conflict, promote resilience and the development of life projects among young people, and how these results could be replicated in other similar rural contexts. The methodological approach of the studies was mixed, combining surveys and interviews with 114 participants, including students, parents, teachers and local authorities. In the first phase of the research, the particularities, expectations, capacities, challenges and initial perceptions of the armed conflict were evaluated, as well as the socio-emotional conditions of the students. The findings revealed that young people faced significant difficulties in building long-term life projects, due to the lack of resources, opportunities and the emotional impact derived from the conflict. In this initial phase, an intervention focused on socio-emotional accompaniment activities was implemented to address perceptions and emotions related to violence and post-conflict. In a second phase, a hybrid learning ecosystem was implemented that integrated digital tools and face-to-face methodologies. These activities were designed to strengthen both the socio-emotional and cognitive competencies of the participants. Forums, chats, multiple-choice questions, reflective activities, workshops, congresses, group discussions and interactive tasks were carried out, with the aim of promoting critical reflection and dialogue on the experiences of conflict. The results showed a significant improvement in the perception of the armed conflict and in the construction of more resilient life projects among the young participants. The analysis of the data using a linear regression model showed that the hybrid learning ecosystem, by combining face-to-face and digital activities, has a positive impact on perceptions of the armed conflict, improves life projects, and strengthens the socio-emotional skills necessary for peacebuilding in post-conflict rural contexts. This model also turned out to be replicable, suggesting that educational interventions based on hybrid ecosystems can be successfully adapted in other rural communities affected by armed conflict, promoting social inclusion and peacebuilding. This article concludes that educational interventions based on hybrid learning ecosystems are a key tool to transform perceptions of armed conflict, improve young people's life projects, and contribute to peacebuilding in post-conflict rural contexts. It is recommended to continue exploring and expanding these educational innovations, especially those that combine digital and face-to-face components, as they constitute a replicable approach that could be scaled up in other regions affected by similar situations.